Establishment of a Ciliogenesis-Associated Signaling Model for Polycystic Kidney Disease - Ling Lu; Qiuling Liu; Lei Zhi; Xuchun Che; Bo Xiao; Mingxuan Cui; Mingyu Yu; Bing Yang; Jingjing Zhang; Bo Zhang (Kidney & Blood Pressure Research, 2021)
Background: Polycystic kidney disease (PKD) represents the most prevalent inherited progressive kidney disorder in humans. Due to complexity of the genetic network behind the disease, the molecular mechanisms of PKD are still poorly understood yet. Objectives: This study aimed to develop a ciliogenesis-associated gene network for PKD patients and comprehensively understand the molecular mechanisms underlying the disease. Method: The potential hub genes were selected based on the differential expression analysis from the GEO database. Meanwhile, the primary hub genes were further elucidated by both in vivo and in vitro experiments. Results: In this study, we established a comprehensive differentially expressed genes profile (including GNAS, PI4KB, UMOD, SLC7A13, and MIOX) for PKD patients compared with the control specimen. At the same time, enrichment analysis was utilized to demonstrate that the G-protein-related signaling and cilia assembling signaling pathways were closely associated with PKD development. The further investigations of the interaction between 2 genes (GNAS and PI4KB) with in vivo and in vitro analyses revealed that PI4KB functioned as a downstream factor for GNAS and spontaneously activated the phosphorylation of Akt into p-Akt for ciliogenesis in PKD formation. The PI4KB depletion mutant zebrafish model displayed a PKD phenotype as well as absence of primary cilia in the kidney. Conclusions: Collectively, our work discovered an innovative potential signaling pathway model for PKD formation, which provided a valuable insight for future study of the mechanism of this disease.